Adsorption potential of CuO-embedded chitosan bead for the removal of acid blue 25 dye - Ismaila Olalekan Saheed; Nuraliah Irdina Zairuddin; Syaza Atikah Nizar; Megat Ahmad Kamal Megat Hanafiah; Ahmad Faiz Abdul Latip; Faiz Bukhari Mohd Suah (Ain Shams Engineering Journal, 2024)
Anthraquinone-based anionic dyes like acid blue 25 (AB25) are among the problematic class of pollutants in wastewaters that are detrimental to human health and aquatic organisms. Chitosan (CS), a biopolymer with rich amino and hydroxyl groups is a potential adsorbent for anionic dye but its instability in acidic medium is its major drawback. In this work, the potential of an innovative and sustainable chitosan-copper oxide bead (CS-CuO) developed to adsorb AB25 from aqueous environment was assessed. The batch adsorption process was studied for significant operational variables, and the CS-CuO was methodically characterised using XRD, FTIR, TGA, SEM and EDX. Unlike CS, the prepared CS-CuO was stable in an acidic and basic medium. XRD pattern of CS-CuO revealed an amorphous and crystalline phase. The micrograph of CS showed a non-porous membranous surface, while CS-CuO shows a relatively rough and irregularly shaped sheet-like structure perforated with pores network. The functional groups O−H, C═O, C−O and N−H on the CS-CuO support its attachment to AB25 dye as reflected in change of absorption signals on FTIR spectra. Electrostatic attraction between AB25 and CS-CuO was most favoured at pH 6 where highest AB25 removal occurs. The adsorption capacity of 294.1 mg/g was obtained for the adsorption process at initial dye concentration of 100 mg/L at pH 6. Langmuir isotherm model and pseudo-second-order kinetics best described the adsorption. The spent CS-CuO was better regenerated in the basic solution (0.1 M NaOH), and its reusability gave 80 % desorption capacity at 3rd cycle.